Role of China's agricultural water policy reforms and production technology heterogeneity on agriculture water usage efficiency and total factor productivity change - Wasi Ul Hassan Shah; Gang Hao; Rizwana Yasmeen; Hong Yan; Jintao Shen; Yuting Lu (Agricultural Water Management, 2023)
China introduced the ''agricultural water conversion policy'' in 2012 to efficiently utilize agricultural water resources and improve production technology in different regions of the Country to increase sustainable agriculture production. To this end, for Policy impact evaluation, our study employed slack-based measure data envelopment analysis, Meta frontier Analysis, and the Malmquist productivity index to measure the agriculture water usage efficiency, agriculture Production technology heterogeneity, and total factor productivity change in pre- and post-agriculture water policy (2012) implementation in different regions of China. Data for 31 provinces and cities were taken for efficiency and productivity estimation from 2000 to 2020. Results revealed that agriculture water usage efficiency significantly increased after the policy implementation. The average agricultural water usage efficiency score for the 2000–2012pre–policy period is 0.6763, whereas the average AWUE score for the 2013–2020 post–policy period is 0.7522, showing an increase of 11.22%. Further results show that the eastern region maintains superior agriculture production technology compared to the western and central regions, with an average technology gap ratio of 0.8941 during the study period. The average total factor productivity change for the study period is 1.0769. Technological change is the primary determinant of productivity growth. There was a marginal decline in average Productivity change after policy implementation. Mann-Whitney and Kruskal Wallis test strengthens the study's results by providing statistically significant differences among different periods and regions.